Visitor Satisfaction and Place Attachment in National Parks - Smith, L.; Ramkissoon, Haywantee; Kneebone, S. (Croatian National Tourist Board, 2014)
This study examines the relationships between visitor satisfaction and place attachment. Confirmatory factor analysis and structural equation modeling were used to test competing models of visitor satisfaction and place attachment represented as a (i) unidimensional, (ii) first-order, and (iii) second-order factor. Data were collected from a sample of 525 visitors at the Bruce Peninsula National Park, in the state of Ontario, Canada. Results indicate visitor satisfaction is a better predictor of place attachment as a second-order construct. Findings are discussed with respect to their applied and theoretical relevance. Practical applications of the study include strategies aimed at achieving optimum visitor satisfaction and promoting place attachment in national parks.